PENGARUH PEMBERDAYAAN SDM DAN MOTIVASI KERJA UNTUK MENINGKATKAN KINERJA KARYAWAN DI SPICE BEACH CLUB - Anak Agung Ngurah Restu Gautama; Komang Arni Fitriani (STKIP Persada Khatulistiwa Sintang, 2025)
Tourism is an industry that is highly dependent on human existence. It consists of interactions between individuals who travel as consumers and as producers, namely the parties that produce tourism goods and services. Human resources are the most important part of an organization, especially for companies that involve many employees. The method used in this study is quantitative. Data collection was carried out by distributing questionnaires to employees. Data analysis using the SPSS (Statistical Package For Social Sciences) analysis method includes validity, reliability, classical assumptions, multiple linear regression, multiple correlation analysis and hypothesis testing. The results show a decrease in employee performance and that employees remain enthusiastic if they work using the abilities, knowledge, and skills that are given a sense of trust and appreciation, their performance can increase in making decisions about their daily activities as employee empowerment. The researcher's suggestion is that increasing employee performance, of course, with the encouragement of work from the company's leadership, can also affect the progress of a company and empowerment of human resources and company work motivation are two factors that can improve employee performance.